Sêrat Bayanullah: Raden Panji Natarata’s Theological Da’wah Rhetoric through Classical Javanese Literature - Mila Indah Rahmawati; Wakit Abdullah Rais; Prasetyo Adi Wisnu Wibowo (Khazanah Theologia, 2022)
This study discusses the wise advice related to Sufism aspects conveyed by Raden Panji Natarata which is packaged in Sêrat Bayanullah based on the character of each têmbang. The purpose of this research is to describe Raden Panji Natarata’s mindset as outlined in the rhetoric of têmbang-têmbang macapat. The method employed descriptive qualitative. The results showed that Raden Panji Natarata was quite skilled at mixing and matching his stories into a da’wah field according to the characteristics of the têmbang. Of the various têmbang macapat presented in this Sêrat Bayanullah, Raden Panji Natarata did not use têmbang durma. This was because têmbang durma has a character that tends to be harsh and angry so that it is not in accordance with the content of the da’wah proclaimed by Raden Panji Natarata. Thus, this locality nuanced da’wah element has an aesthetic and humanistic impression. As the title embedded in this literary work, Sêrat Bayanullah means the explanation of the chapter of Allah. Thus, it is hoped that this literary work can be a reference for understanding the nature of the chapter of Allah.